The Optimization of Blended Learning in Extensive and Intensive Reading Course - Musdalifah, Musdalifah (Majesty Journal, 2020)
This study aimed to describe 1) the application of Blended Learning to extensive and intensive reading subjects, and 2) the student perception of the optimization of blended learning. The subject of this study was the students of the Department of English Education at the Muhammadiyah University of Enrekang. The data in this analysis were the behaviors of students and lecturers in the teaching and learning process and the students' understanding of the learning process in the classroom. The findings showed that (1) students and lecturers were regularly involved in live learning and online interaction, and (2) students had a good view of learning.